Becoming a guest in your own home: Home care in Sweden from the perspective of older people with multimorbidities. (30th March 2018) - Jarling, Aleksandra; Rydström, Ingela; Ernsth‐Bravell, Marie; Nyström, Maria; Dalheim‐Englund, Ann‐Charlotte
Abstract : Aim and objective: To describe the meaning of the phenomenon home care from the perspective of older persons who live alone with multimorbidity. Background: In line with worldwide changing demographics, conditions for older people in need of home care are changing. In Sweden there is a stay‐in‐place policy and older people are expected to live and be cared for in their own home as long as possible. Home care, instituted by different laws, is a challenge affecting the older person when the private home becomes a workplace. Design: This study uses a qualitative design with a lifeworld approach. Methods: The study having been conducted in Sweden in 2016, the researchers interviewed 12 older persons that live alone and receive home care. Data were analysed using qualitative content analysis. Results: The findings illustrate four sub‐themes: adapting to a caring culture, feeling exposed, unable to influence care and forced relations. The overall theme reveals that older people experience a life‐changing situation when receiving home care and they become a guest in their own home. Conclusions: Becoming older with increased needs means to disrupt one's life when one's private home becomes a public arena. The gap between an older person's rights by law and the older person's experiences of receiving home care needs to be highlighted to meet the oncoming challenges in providing a home care that includes participation of the older themselves. Only then can care be offered that enables older people to have a sense of control and experience their home as their own. Implications for practice: The findings emphasise the need to view older people as being self‐determinant and independent. Older people receiving home care need to be seen as individuals, and their entire life situation should be considered by also acknowledging the important role played by relatives and caregivers.